PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN CUSTOMER DI CHECK IN COUNTER BANDARA TEBELIAN SINTANG - Ramadhani, Ayumi Safara; Wakhidah, Esti Nur (Growth, 2022)
Check-in counters are airport staff or officers in charge of providing services to passengers who carry out the check-in process at the departure terminal, this service is included in the pre-flight service that passengers receive when traveling using air transportation. Therefore, the quality of service affects the smoothness of the flight. This study aims to determine the effect of service quality on customer satisfaction at the check-in counter at the Tebelian Sintang airport. This research uses quantitative research. The data collection method used a questionnaire which was distributed to the passengers at the tebelian sintang airport. The data was processed with SPSS (Statistical Product and Service Solutions) to test the research instruments, hypotheses, classical assumptions and multiple linear regression. The results showed that simultaneously the quality of tangible, responsiveness and empathy services had no effect on customer satisfaction at the check-in counter at Tebelian Sintang airport with a significant value <0.05. while the quality of service reliability and assurance simultaneously affect customer satisfaction at the check-in counter at tebelian sintang airport with a significant value > 0.05.